Cost of youth tobacco-control policies in seven European countries. (18th September 2019) - Leão, Teresa; Perelman, Julian; Clancy, Luke; Hoffmann, Laura; Kinnunen, Jaana M; Mélard, Nora; Nuyts, Paulien A W; Richter, Matthias; Rimpelä, Arja; Lorant, Vincent; Kunst, Anton E
Abstract: Background: Tobacco-control policies have been suggested to reduce smoking among adolescents. However, there is limited evidence on the real-world costs of implementation in different settings. In this study, we aimed at estimating the costs of school smoking bans, school prevention programmes and non-school bans (smoking bans in non-educational public settings, bans on sales to minors and bans on point-of-sale advertising), implemented in Finland, Ireland, the Netherlands, Belgium, Germany, Italy and Portugal, for 2016. Methods: We retrospectively collected costs related to the inspection, monitoring and sanctioning activities related to bans and educational activities related to smoking prevention programmes. We used an 'ingredients-based' approach, identifying each resource used, quantity and unit value for one full year, under the state perspective. Costs were measured at national, regional, local and school-level and were informed by data on how these activities were performed in reality. Results: Purchasing power parities adjusted-costs varied between €0.02 and €0.74 (average €0.24) per person (pp) for bans implemented outside schools. Mean costs of school smoking bans ranged from €3.31 to €34.76 (average €20.60), and mean costs of school educational programmes from €0.75 to €4.65 (average €2.92). Conclusions: It is feasible to estimate costs of health policies as implemented in different settings. Costs of the tobacco control policies evaluated here depend mainly on the number of person-hours allocated to their implementation, and on the scale of intervention. Non-school bans presented the lowest costs, and the implementation of all policies cost up to €36 pp for 1 year.